Specificities and Opsonophagocytic Activities of Antibodies to Pneumococcal Capsular Polysaccharides in Sera of Unimmunized Young Children - Soininen, Anu (American Society for Microbiology, 2002)
An enzyme immunoassay (EIA) for antibodies to pneumococcal capsular polysaccharides (Pnc PSs) detects in some cases antibodies that are cross-reactive within different Pnc PSs. Recently, it has been suggested that for detection of only serotype-specific antibodies, EIA can be modified by removing cross-reactive antibodies by absorption with an irrelevant PS, e.g., the type 22F PS. The opsonophagocytosis assay measures the functional activities of antibodies in vitro, and the results of that assay correlate with in vivo protection better than measurement of the antibody concentration by EIA. We compared these different methods for measuring antibodies to type 1, 6B, 11A, 14, 19F, and 23F Pnc PSs in the sera of unimmunized young children who had been monitored for pneumococcal carriage, acute otitis media, and acquisition of antibodies to Pnc PSs from 2 to 24 months of age. Serum samples with antibody increases after contact with a pneumococcus of a homologous serotype contained specific antibodies and often had opsonophagocytic activity (OPA) (20 of 46). In samples with antibody increases from children who had not had contact with a pneumococcus of a homologous serotype, the antibodies found to be type specific by conventional EIA were usually cross-reactive and infrequently had OPA (10 of 68). When type 22F PS absorption was used in the EIA, most of the false antibody increases were eliminated, but most of the true antibody increases were still detected and the association between the antibody concentration detected by EIA and OPA was improved. However, there were serotype-dependent differences in the frequency of OPA. Use of absorption with a heterologous PS in EIA should be encouraged, and both the specificity of EIA and the sensitivity of opsonophagocytic assays should be further evaluated and improved.